Probabilistic Calculation of Tolerances of the Dimension Chain Based on the Floyd-warshall Algorithm - Muholzoev, A.V.; Masyagin, V.B. (Procedia engineering, 2016)
The tolerance analysis of the technological processes in mechanical engineering is a time-consuming task requiring automation. Development of an algorithm to identify individual dimension chains makes this task even more difficult. Based upon this, one must create an algorithm to avoid the difficulties of the algorithmization procedure. An approach to the calculation of the probability of closing tolerance units is based on the Floyd-Warshall algorithm – a classical algorithm of the graph theory, which calculates the length of the paths in the graph by adding the lengths of the links in pairs. The algorithm allows calculation without identifying individual dimension chains solving the entire structure of the complex. This approach can significantly simplify the implementation of the computer-aided calculation of dimensional circuits.